2D photonic crystal logic gates based on self-collimated effect. (21st July 2016) - Fan, Ranran; Yang, Xiulun; Meng, Xiangfeng; Sun, Xiaowen
Abstract: Four kinds of logic gates are proposed using interference between the self-collimated beams in photonic crystals, namely NOT, OR, AND and XOR gates, which can be used in the design of photonic integrated circuits. The radius of the splitter and the optical path difference between splitters are adjusted to produce certain phase difference between the reflected and transmitted beams, which may interfere constructively or destructively to realize logical operation. They have high contrast ratios and low power consumption, the extinction ratio between logic 1 and logic 0 for NOT and AND gates can reach 24.7 dB, 30 dB and 12.6 dB for the wavelength used by optical communication (1550 nm), respectively, which makes it potentially applicable for photonic integrated circuits.